Assessing Fiscal Sustainability Under Uncertainity - Barnhill, Theodore (IMF Working Papers; Working Paper ;, 2003)
Unlike conventional fiscal sustainability assessments, the Value-at-Risk approach developed in this paper explicitly captures the contribution of key risk variables to public sector vulnerability. In an illustrative application to Ecuador, the VaR approach confirms a significant risk of government financial failure stemming from the volatility and comovements of the exchange rate, interest rates, oil prices, and output. Although dollarization has helped attenuate fiscal vulnerability, the volatility of sovereign spreads and of oil prices remain major sources of risk for Ecuador's public sector. The paper concludes with a discussion of policy implications, an evaluation of the methodology, and suggestions for future research.